Corynebacterium striatum: A True Pathogen in Chronic Contiguous Osteomyelitis - Grishma R. Trivedi; Shehzad S. Merchant (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective/Purpose. Chronic contiguous osteomyelitis (CCO) is a well-recognized clinical condition. Causative factors include direct trauma, prior surgery, or underlying comorbidities like diabetes and vascular insufficiency. Staphylococci especially S. aureus, Streptococci especially beta-hemolytic Streptococci, Gram-negative bacilli, and anaerobes are the most common pathogens isolated. Corynebacterium striatum (C. striatum) is a ubiquitous Gram-positive rod that colonizes the skin and mucous membranes of normal hosts and hospitalized patients. The pathogenic potential of C. striatum has only been reported in immunocompromised hosts and in patients with retained foreign bodies and prosthetic devices. However, it is not a known causative agent of chronic contiguous osteomyelitis. Design/Method. We recognized seven cases of CCO whereby amidst polymicrobial growth, C. striatum appeared to be a true pathogen and required targeted treatment along with surgical intervention. Main Outcome Measures. A pre-post analysis was used to assess the outcome. Results. All patients were cured after successful completion of an antibiotic course with a resolution of infection. Cure was defined as granulation of the infected wound and resolution of clinical symptoms at outpatient follow-up between 6 and 8 weeks. Conclusion. This series emphasizes that C. striatum is often a true pathogen in the setting of CCO. When isolated in polymicrobial infections, a targeted antibiotic therapy towards this pathogen along with other causative pathogens accompanied by surgical intervention is typically required for a successful cure of CCO.